The Changing Structure of Chinaâs Pearl River Delta Megacity Region - Song, Junru; Zhao, Min (The ITB Journal Publisher, 2018)
Based on traditional spatial gravity interaction models, urban quality and the time it takes for people or goods to move between cities are strongly correlated and the extent to which cities are integrated or have the capacity to become integrated into an interconnected urban network changes as travel time between cities changes. This paper analyses Chinaâs Pearl River Delta (PRD) megacity region based on a modified gravity model combined with spatial analysis. It also analyzes economic relations between cities within the PRD megacity region, and compares Chinaâs recent ânew-styleâ urbanization planning in Guangdong Province â the regionâs largest and economically most important province â with planning for Guangdong that pre-dated Chinaâs 2014 National New Style Urbanization Plan. The results show that PRD is now a bi-polar megacity region dominated by Guangzhou and Shenzhen and that four out of six cities the province planned to integrate into the core after 2005 have been integrated, but two have not. In order to build a successful global urban region, PRD needs to continue to improve its core, accelerate the integration of city clusters that can realistically be integrated, continue to study the integration potential of cities with less development potential and pay attention to balanced development of peripheral cities.Keywords. Pearl River Delta, the gravity model, economic spatial connection.Abstrak. Berdasarkan model interaksi gravitasi spasial tradisional, kualitas perkotaan sangat berhubungan dengan waktu tempuh untuk manusia dan barang berpindah dari satu kota ke kota yanglain. Selain itu juga tergantung sejauh mana kota-kota terintegrasi atau memiliki kapasitas untuk terintegrasi ke dalam perubahan jaringan perkotaan yang saling terhubung disebabkan oleh perubahan waktu perjalanan antar kota. Makalah ini menganalisis kawasan mega region Pearl River Delta (PRD) Cina berdasarkan pada model gravitasi yang dimodifikasi yang dikombinasikan dengan analisis spasial. Makalah ini juga menganalisa hubungan ekonomi di antara kota-kota di dalam wilayah megaregion PRD, dan membandingkan perencanaan urbanisasi